Early and Delayed Infarct Growth in Patients Undergoing Mechanical Thrombectomy: A Prospective, Serial MRI Study. Issue 1 (3rd November 2022) - Hernández-Pérez, María; Werner, Mariano; Remollo, Sebastián; Martín, Carlota; Cortés, Jordi; Valls, Adrian; Ramos, Anna; Dorado, Laura; Serena, Joaquin; Munuera, Josep; Puig, Josep; Pérez de la Ossa, Natalia; et al.
Abstract : Background: We studied the evolution over time of diffusion weighted imaging (DWI) lesion volume and the factors involved on early and late infarct growth (EIG and LIG) in stroke patients undergoing endovascular treatment (EVT) according to the final revascularization grade. Methods: This is a prospective cohort of patients with anterior large artery occlusion undergoing EVT arriving at 1 comprehensive stroke center. Magnetic resonance imaging was performed on arrival (pre-EVT), <2 hours after EVT (post-EVT), and on day 5. DWI lesions and perfusion maps were evaluated. Arterial revascularization was assessed according to the modified Thrombolysis in Cerebral Infarction (mTICI) grades. We recorded National Institutes of Health Stroke Scale at arrival and at day 7. EIG was defined as (DWI volume post-EVT–DWI volume pre-EVT), and LIG was defined as (DWI volume at 5d–DWI volume post-EVT). Factors involved in EIG and LIG were tested via multivariable lineal models. Results: We included 98 patients (mean age 70, median National Institutes of Health Stroke Scale score 17, final mTICI≥2b 86%). Median EIG and LIG were 48 and 63.3 mL in patients with final mTICI<2b, and 3.6 and 3.9 cc in patients with final mTICI≥2b. Both EIG and LIG were associated with higher National Institutes of Health Stroke Scale at day 7 ( ρ =0.667; P <0.01 and ρ =0.614; P <0.01, respectively). In patients with final mTICI≥2b, each 10% increase in the volume of DWI pre-EVT and each extra pass leaded to growths of 9% (95% CI, 7%–10%) and 14% (95% CI, 2%–28%) in the DWI volume post-EVT, respectively. Furthermore, each 10% increase in the volume of DWI post-EVT, each extra pass, and each 10 mL increase in TMax6s post-EVT were associated with growths of 8% (95% CI, 6%–9%), 9% (95% CI, 0%–19%), and 12% (95% CI, 5%–20%) in the volume of DWI post-EVT, respectively. Conclusions: Infarct grows during and after EVT, especially in nonrecanalizers but also to a lesser extent in recanalizers. In recanalizers, number of passes and DWI volume influence EIG, while number of passes, DWI, and hypoperfused volume after the procedure determine LIG.